Application of modified model predictive control to a gantry system - Askari, M.; Mohamed, H.A.F.; Moghavvemi, M.; Yang, S.S. (2009)
This paper considers in particular the design of a controller based on model predictive control and feedback linearization methods for gantry systems. In order to meet the operation requirements of fast anti-swaying and precise positioning of gantry crane systems, a practical optimal control scheme is presented. This controller is designed to guarantee the performance in presence of a class of nonlinear dynamics. The controller is implemented on an experimental rotary gantry system. The controller achieves good positioning accuracy and significant sway reduction.